The implications of the libraries social environments on library policy and management - Kaegbein, Paui; Wang, Wao (Information & Media, 1994)
The article opens a discussion about broader and deeper techniques for discourse analysis taking into consideration the interdisciplinary trend and suggesting an integrated programme for the analysis of a political discourse characteristic of a political leader. The programme is designed as a model for the text analysis of social documents and based on the causal-genetic theory developed by the author.
Keywords: discourse; causal-genetic theory applied to the content of a text; subject representation in categories of discourse; operationalisation of discourse categories